2020
DOI: 10.5937/psistra23-25971
|View full text |Cite
|
Sign up to set email alerts
|

Big Five traits as (mal)adaptive behavioural responses to harsh and unpredictable environment: Further evidence for the state-dependent evolution of personality

Abstract: State-dependent behaviour models of personality predict that fitness consequences of personality depend on various states. Hence, personality traits may be adaptive only in certain conditions. In the present research, we tested the state-dependent personality model of Big Five personality traits using harsh and unpredictable environments as the extrinsic states. The data were collected on a community sample (N=221). We extracted the fitness factor from a broader set of indicators related to reproduction and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(55 reference statements)
0
1
0
1
Order By: Relevance
“…crta ličnosti od kojih je svaka, u nekoj mjeri, prisutna kod svakog pojedinca. Ličnost je ono što omogućava predviđanje šta će osoba uraditi u određenoj situaciji (Cattel, 1950: 2-3), određena je postojanjem individualnih razlika u obrascima ponašanja (Međedović, 2020), a osobine ličnosti se odnose na dosljedne obrasce načina na koji se pojedinci ponašaju, osjećaju i misle (Pervin et al, 2008) i koje su stabilne tokom vremena (Fredenburgh, 1971;Larsen i Buss, 2008).…”
Section: Pregled Istraživanja Osobina Ličnosti Vođeunclassified
“…crta ličnosti od kojih je svaka, u nekoj mjeri, prisutna kod svakog pojedinca. Ličnost je ono što omogućava predviđanje šta će osoba uraditi u određenoj situaciji (Cattel, 1950: 2-3), određena je postojanjem individualnih razlika u obrascima ponašanja (Međedović, 2020), a osobine ličnosti se odnose na dosljedne obrasce načina na koji se pojedinci ponašaju, osjećaju i misle (Pervin et al, 2008) i koje su stabilne tokom vremena (Fredenburgh, 1971;Larsen i Buss, 2008).…”
Section: Pregled Istraživanja Osobina Ličnosti Vođeunclassified
“…The propensity would be global or local, as the body state tunes to environmental aspects variously including physical, chemical, biological and social contexts. Studies in animals [49] and humans [50,51] have shown that the individual behavior will be different depending on the core body state, with relations to fitness. Personality could emerge as an adaptation to individual differences in core state variables [52][53][54].…”
Section: Body State Deviating Integrity Assessedmentioning
confidence: 99%